Assessing impact of mesoscale eddy processes in coarse resolution ocean models - Riaz, A (2021)
Mesoscale eddies, not only in the Southern Ocean but globally, play a vital role in mixing and transporting climatically important tracers such as heat and carbon dioxide. Nearly all the ocean models used for climate studies run at a non-eddy-resolving horizontal resolution of 1¬¨‚àû or coarser, and therefore the effects of eddies (advection and mixing) are parameterised in these models. In some models, this parameterisation is employed as a spatially uniform value while other models employ varying advection and mixing parameterisations. However, observations show that it is spatially non-uniform. Recently developed, suppressed mixing length theory takes into account eddy propagation relative to the background mean flow which suppresses the mixing rates - Ferrari and Nikurashin, (2010). Observations have also shown the evidence of suppression of mixing (Naveira Garabato et al., 2011; Roach et al., 2018). The research on suppressed eddy mixing has revealed that mixing rates vary spatially and impact tracer transport. An improved parameterisation of eddy mixing which considers the spatial variability of eddy mixing could improve our understanding of the response of the global ocean to tracer uptake and climate change. Here we test the competing parameterisations. We do this assessment in Python Ocean Model (pyOM2.2), with a closed energy cycle where the energy available for the mixing in the ocean is only controlled by the external energy input from the atmosphere, tidal system, and internal exchanges. Currently none of the other ocean models used for climate projections use such an energy consistency framework. First, the parameterisation of suppressed eddy mixing is implemented in an idealised model configuration of the Antarctic Circumpolar Current in a zonally symmetric periodic channel. This study of an idealised channel model suggests that suppressed eddy mixing parameterisation performs better than the traditionally used parameterisations (spatially uniform and unsuppressed), in the context of tracer ...